2020
DOI: 10.3389/feart.2020.00234
|View full text |Cite
|
Sign up to set email alerts
|

Holocene East Asian Summer Monsoon Rainfall Variability in Taiwan

Abstract: Characterizing the spatiotemporal variability of the East Asian summer monsoon (EASM) advances our understanding of its rhythm, dynamics, and future impacts. East Asian summer monsoon variations during the Holocene have been reconstructed from a variety of geological archives and proxies. However, the spatiotemporal heterogeneity of EASM rainfall during the Holocene remains controversial. Taiwan is geographically suitable for studying the EASM history, through its geological archives. Herein, we synthesize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 124 publications
(234 reference statements)
0
4
0
Order By: Relevance
“…in sea level (Figure 9). The increase in Mz and L* during the period 8.2-11.55 ka BP with the SST and PJJA records (Ding et al, 2020) suggests that the regional sedimentary record during this period is less sensitive to the effects of global climate change, but can still reflect solid climatic fluctuations. The early part of MIS 1 (8.75-11.55 ka BP) has a warmer and wetter climate and can be identified as a period of marginal beach deposition and floodplain accretion.…”
Section: Response Of Sedimentary Environment To Climate and Sea-level...mentioning
confidence: 93%
See 1 more Smart Citation
“…in sea level (Figure 9). The increase in Mz and L* during the period 8.2-11.55 ka BP with the SST and PJJA records (Ding et al, 2020) suggests that the regional sedimentary record during this period is less sensitive to the effects of global climate change, but can still reflect solid climatic fluctuations. The early part of MIS 1 (8.75-11.55 ka BP) has a warmer and wetter climate and can be identified as a period of marginal beach deposition and floodplain accretion.…”
Section: Response Of Sedimentary Environment To Climate and Sea-level...mentioning
confidence: 93%
“…In addition, combined with climate-sea level change records, precipitation, temperature, and sporulation records from Chaohu Lake (Wang et al, 2008) are found around 8.75 ka BP, indicating the onset of a rapid temperature rise synoptic event at this time and a significant sea level rise in eastern China (Zheng, 2018), consistent with regional alluvial phase deposition under strong hydrodynamic conditions. In contrast, the d 18 O of NGRIP, d 18 O of Dongge Cave, SST, and PJJA records highlight the Younger Dryas impact hypothesis event at 11.2 ka BP, with a sharp drop in temperature, with cold-dry climate and a brief drop in sea level (Zhang et al, 2004;Praetorius et al, 2015;Ding et al, 2020;Walczak et al, 2020).…”
Section: Response Of Sedimentary Environment To Climate and Sea-level...mentioning
confidence: 99%
“…The precipitation in most parts of China is influenced by the Asian monsoon (divided into two subsystems, the East Asian Monsoon and the Indian Monsoon), especially the East Asian summer monsoon (Ding et al, 2008). NC and the UH are located in the main rain bands of the East Asian summer monsoon; the advance and retreat of the East Asian summer monsoon are accompanied by the movement of the rain bands, which influences the changes in precipitation, droughts and floods in NC and the UH (Ding et al, 2020). It was found that during the period of the 1950s-1970s, when the East Asian summer monsoon was abnormally strong, China's rain bands moved northwards, and NC was relatively wet; after the late 1970s, the East Asian summer monsoon weakened significantly, the rain bands moved southwards, and NC was relatively dry (Gong & Ho, 2002;Zhai et al, 2005).…”
Section: Possible Climatic Factors Influencing the Co-drought In Nc A...mentioning
confidence: 99%
“…Within the age uncertainty estimates, our IMF6+7 + 8 record of Core CF1 is broadly consistent with the abovementioned proxy evidence and suggests a slow-down of the KC during the period of 4.6-2.0 ka, followed by quickly enhanced KC and attaining the highest level at approximately 0.5 ka (Figure 6A). Additionally, climate records from the Taiwan Island (Selvaraj et al, 2007;Ding et al, 2020), SST of Core ZY2 (Wang et al, 2011). (C) ESNO events per 100-years (Moy et al, 2002).…”
Section: Long-term Trend Of Kuroshio Current During the Late Holocene...mentioning
confidence: 99%